Controversy of Marriage Agreements in Indonesia-Malaysia Border Communitites in Sambas Regency - Asman Asman; Resali bin Muda (El-Mashlahah, 2023)
This study discusses the controversy over the marriage agreement in the form of taklik talak contained in the marriage book. The purpose of this study was to analyze the pros and cons of the reading of taklik talak on the bride and groom after consent was granted in the Indonesia-Malaysia border community in Sambas Regency, West Kalimantan. The method in this study is to use empirical legal research with a sociological approach. Primary data was obtained using observation, interview, and documentation techniques. The results of this study indicate that of the ten respondents interviewed six couples did not know the existence of a marriage agreement (taklik talak) and did not pronounce it. while the other four couples did not know the taklik talak but recited it. The occurrence of pros and cons to the existence of taklik talak in the marriage book is due to the lack of information submitted by the BP4 during premarital guidance to the prospective bride and groom, besides that, some people do not know the use and purpose of taklik talak. Whereas the existence of taklik talak as a marriage agreement aims to protect the rights of the wife so that the husband does not arbitrarily fulfill his obligations. The marriage agreement contained in the taklik talak is in line with Islamic law.